2013
DOI: 10.1021/jp4098974
|View full text |Cite
|
Sign up to set email alerts
|

Pnicogen Bonds: A Theoretical Study Based on the Laplacian of Electron Density

Abstract: Although, most of the authors classify the pnicogen bonds as σ-hole bonding, there are some evidence that show they do not require any positive electrostatic potential around interacting molecules. In this work, the Laplacian of electron density is used to study pnicogen bonds in different dimer and trimer complexes. It is shown that the noncovalent P···P, P···N, and N···N bonds can be categorized as lump-hole interactions; a region of charge depletion and excess kinetics energy (hole) in the valence shell cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…24 Another study on pnicogen bonding categorized it as lump-hole interactions. 41 The study on pnicogen bonded complexes involving anions showed the presence of some covalent character in these interactions. 42 The strength of pnicogen bonds involving N, P, and As was also investigated and it was observed to be highly stabilizing.…”
Section: Introductionmentioning
confidence: 99%
“…24 Another study on pnicogen bonding categorized it as lump-hole interactions. 41 The study on pnicogen bonded complexes involving anions showed the presence of some covalent character in these interactions. 42 The strength of pnicogen bonds involving N, P, and As was also investigated and it was observed to be highly stabilizing.…”
Section: Introductionmentioning
confidence: 99%
“…This space region is thus prone to interact with the lone electron pair(s) carried by the partner. Recently, a similar analysis (also valid for homologous noncovalent bonds) has been proposed using, as the primary physical observable, the electron density Laplacian ∇ 2 ρ(� r) [25][26][27][28] instead of MEP, leading to the so-called lump-hole interaction paradigm [29]: the electron-deficient region at the periphery of the halogen atom is then viewed as a "hole" that can be filled by the electron-rich Lewis base's lump. Indeed, it is very well known that charge depletion areas are easily characterized by positive ∇ 2 ρ(� r) values, while charge concentration occurs when ∇ 2 ρ(� r) is negative.…”
mentioning
confidence: 99%
“…These interactions can be divided into σ–hole [ 21 , 22 , 23 , 24 ] and π–hole interactions [ 25 , 26 , 27 , 28 , 29 ] and are nowadays entered into the toolkit supramolecular chemists. Actually, tetrel (Tt) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], pnictogen (Pn) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], and chalcogen (Ch) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] bonding interactions (see Figure 1 ) have been studied by many theoretical works and are progressively used experimentally in relevant fields such as supramolecular catalysis, polymers, transmembrane ion transport and, especially, crystal engineering [ 15 , …”
Section: Introductionmentioning
confidence: 99%